The Sonodegradation of a Petrochemical Industry Wastewater - Rukiye Oztekin; Delia Teresa Sponza (The Global Environmental Engineers, 2019)
In this study, the effects of increasing sonication times (0 min, 60 min, 120 and 150 min), sonication temperatures (25oC, 30oC and 60oC), increasing titanium dioxide (TiO2) (0.1 mg/L, 0.5 mg/L, 10 and 20 mg/L), sodium chloride (NaCl) (1 g/L, 2.5 and 15 g/L), ferrous ion (Fe+2) (2 mg/L, 8 and 20 mg/L) and ferric ion (Fe+3) (10 mg/L, 20 and 50 mg/L) concentrations on the dissolved chemical oxygen demand (CODdis), total organic carbon (TOC) and total polycyclic aromatic hydrocarbons (PAH) removal efficiencies were monitored at a sonication frequency of 35 kHz and a sonication power of 640 W for a raw petrochemical industry wastewater (PCI ww). As the sonication time and temperature were increased from 60 to 120 and 150 min, and from 25 oC to 30 oC and to 60 oC, the CODdis, total PAH and TOC yields increased from around 52-58% and 69%-72% to 80-87% and 78%-90%. The maximum CODdis, total PAH and TOC yields were obtained with 20 mg/l TiO2, 15 mg/l NaCl, 20 mg/L Fe+2 and with 50 mg/L Fe+3, particularly after 150 min sonication at 60 oC. However, it is important to note that after 150 min sonication in the samples free of the chemicals mentioned above, in other words, in the samples with only sonication exhibited high yields as is the samples added the chemicals. After sonication with the chemicals, the EC50 values decreased significantly versus sonication times. The maximum Daphnia magna acute toxicity removal yield was 99.91% at NaCl=1 g/L at 60oC after 150 min sonication.